TRADE SECTOR CHALLENGES, OPPORTUNITIES AND STRATEGIES IN EAST JAVA PROVINCE DURING THE COVID-19 PANDEMIC - Diana Rapitasari; I Made Bagus Dwiarta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The Covid-19 pandemic is sweeping the world, and Indonesia is one of the countries affected. Indonesia is combating Covid-19 by converting its regional quarantine (lockdown) policy into large-scale social restrictions (PSBB) that are local in nature and vary depending on the severity of the province, district, or city. During the pandemic, the global economy and Indonesia both slowed. According to the government and strategic assessment institutions, Indonesia's growth will be low, if not negative, in 2020. Nobody knows when this pandemic will end. Various problems that have begun to emerge are the latest challenge for the government to improve the country's economic stability. Because of this, As a result, the East Java Provincial Government is attempting to implement a number of economic strategies in order to avoid a prolonged crisis, particularly in the industrial and trade sectors.